The European Union includes agricultural landscape biodiversity targets in its Green Deal strategies and in preparation for the Convention on Biological Diversity - CGIAR Research Program on Water, Land and Ecosystems (2020)
The European Union, as part of its Farm to Fork Strategy and Biodiversity Strategy for 2030, is proposing 10% conservation of natural and semi-natural habitats in agricultural landscapes. WLE researchers contributed significantly to this proposal through their research and engagement with the European Union.